Atypical Presentation of Celiac Disease: A Case Report - Dr. Sunil Kumar; Dr. Amit Sharma (Pediatric Review: International Journal of Pediatric Research, 2018)
Celiac disease is a chronic inflammatory immune-mediated condition associated with small intestinal injury triggered by gluten present in wheat, barley and rye, leading to malabsorption of different nutrients. Usually it presents as young age at the time of introduction of cereals with symptoms of malabsorption like diarrhea, abdominal distension and failure to thrive. But celiac disease has a broad range of general, gastrointestinal and systemic presentation. We hereby present a case of celiac disease presenting as a case of refractory vomiting, responding dramatically to gluten free diet.